Use of protein kinase C and phospholipase A2 inhibitors in bovine endometrial cells treated with estradiol and calcium ionophore - Maldonado, Mariângela Bueno Cordeiro [UNESP]; Henry, Francine Messias Ciríaco; Ferreira, Teissiane Fernanda de Vasconcelos [UNESP]; Mello, Barbara Piffero; Binelli, Mario; Membrive, Claudia Maria Bertan [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
The release of endometrial prostaglandin-F2α (PGF2α) in bovine females can be induced in vivo by estradiol (E2). However, its role in this mechanism has not been clarified. We hypothesized that E2 stimulates the activity and abundance of protein kinase C (PKC) and phospholipase A2 (PLA2). Our objective in this study was to analyze the effects of PKC and PLA2 inhibitors on PGF2α synthesis induced by E2 and calcium ionophore (CI) in bovine endometrial cells (BEND cells; Experiment 1). Additionally, we evaluated the abundance of PKC and PLA2 in endometrial explants of cows treated or not with E2 17 days after estrus (D17, D0 = estrus; Experiment 2). In Experiment 1, BEND cells were submitted to a PKC inhibitor (10 µM of C25 H24 N4 O2; bisindolylmaleimide I, or BIS I), a PLA2 inhibitor (20 µM of arachydoniltrifluoromethane or AACOCF3), or none. The BEND cells were subsequently treated with E2 and CI, and PGF2α concentrations were measured in the culture medium through radioimmunoassay. For DIF-12 (PGF2α concentration 12 h after treatment subtracted from PGF2α concentration at hour 0), no PKC inhibitor effect was observed (P= 0.2709). However, DIF-12 was lower (P < 0.05) for groups treated with the PLA2 inhibitor and PLA2 inhibitor + CI + E2 groups than the control and CI + E2 groups. Thus, AACOCF3 was an efficient PLA2 inhibitor in the BEND cells culture system, and E2 did not stimulate the synthesis of PKC and PLA2. In Experiment 2, cyclic Nellore heifers received none (n = 5) or 3 mg (n = 6) of 17β-E2 on D17 and were slaughtered 2 h after administration. The abundance of PKC and PLA2 in the endometrial tissue was evaluated using Western blotting analysis. No E2 effect was observed on PKC (P = 0.08) and PLA2 (P = 0.56). We concluded that E2 did not stimulate the activity and abundance of PKC and PLA2.
Uso de inibidores de proteína quinase C e fosfolipase A2 em células endometriais bovinas tratadas com estradiol e ionóforo de cálcio
Keywords: BEND cells; Estradiol; PGF2α; PKC; PLA2